Understanding the threats to DNS and how to secure it. (October 2015) - Marrison, Chris
Abstract : Essentially the address book of the Internet, the Domain Name System (DNS) is a mission-critical infrastructure used by all organisations and without which they cannot function. Yet, despite its importance, it remains a vulnerable network component that is frequently used as an attack vector by cyber-criminals, and is inadequately protected by traditional security solutions. The Domain Name System (DNS) is a mission-critical infrastructure that all organisations use and can't function without. But it is a highly vulnerable network component. External DNS servers may be subject to attacks such as DNS DDoS, exploits and reconnaissance, but threats may not always be outside an organisation's firewall. Chris Marrison of Infoblox discusses the importance of securing external DNS from cyber-attacks, as well as securing internal DNS from infrastructure attacks, APTs and malware that exploit DNS, and data exfiltration via DNS.